CO2 emissions from soils of different depths of a permafrost peatland, Northeast China: response to simulated freezing–thawing cycles. Issue 4 (29th April 2014) - Wang, Jiaoyue; Song, Changchun; Hou, Aixin; Wang, Lili
Abstract: Soil freezing–thawing cycle (FTC) is an important factor controlling C dynamics in mid–high latitude regions, especially in the permafrost regions impacted by global warming. Nonetheless, the response of C cycling in the deeper active layers of permafrost regions to FTC remains far from certain. We aimed to characterize the emission of CO2 from soils of multiple depths as impacted by FTC and its relationship with active organic C (OC) and enzyme activities. We collected soil samples from three soil layers (0–15, 15–30, and 30–45 cm) of an undisturbed peatland in the Da Xing'anling Mountains, NE China, and then subjected them to various freezing (10 to –10°C) and thawing (–10 to 10°C) cycles. Soil CO2 emissions, two active OC fractions, and activities of three enzymes were monitored during incubation periods. At the thawing stage of the first FTC, CO2 emission rates in the three soil layers presented transient peaks being ≈ 1.6–1.7 times higher than those of the unfrozen control sample. Although FTC did not change the overall patterns of decreasing CO2 emission along the soil profile, FTC significantly reduced the amount of CO2 emission when compared with the unfrozen control sample, possibly because the small CO2 emission at the freezing stage neutralized the peak of CO2 emission at the thawing stage. This study suggests that in the active layer of permafrost peatlands, CO2 emission during FTCs may be lower than the emission under higher temperatures, but experiment with more temperature gradients should be encouraged to verify this conclusion in the future. Meanwhile, FTC significantly increased water extracted OC release from the three soil layers, ≈ 1.2–1.6 times higher compared to the unfrozen control sample, indicating that soil carbon loss in the form of leachate may increase during freezing–thawing periods. Additionally, the CO2 emissions impacted by FTCs were significantly correlated with active OC fractions and enzyme activities, which indicated that active OC and enzymes were sensitive to FTCs, and surviving microbes and enzymes might use the increased liable substrates and induce the CO2 emission during freezing–thawing periods.